PENGARUH KOMUNIKASI, KOMITMEN ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI INSPEKTORAT KOTA PALU - Darmawan, Riski (Katalogis, 2015)
The aims of this research are : (1) to explore the influence of communication, organizational commitment and motivation on official’s performance in The Inspectorate Office of Palu. (2) to investigate the influence of communication on official’s performance in The Inspectorate Office of Palu, (3) to investigate the influence of organizational commitment on official’s performance in The Inspectorate Office of Palu, (4) to investigate the influence of motivation on official’s performance in The Inspectorate Office of Palu, (5) to investigate the difference between the performance of male and female official’s performance in The Inspectorate Office of Palu. This research is causal descriptive and it focuses on explaining the relations between variables. As many as 48 samples are selected by census sample method, where all population has a change to be chosen as a sample. The results show that : (1) simultaneously communication, organizational commitment and motivation positively and significantly affect the official’s performance in The Inspectorate Office of Palu, (2) communication positively and significantly affect the official’s performance in The Inspectorate Office of Palu, (3) organizational commitment positively and significantly affect the official’s performance in The Inspectorate Office of Palu, (4) motivation positively and significantly affect the official’s performance in The Inspectorate Office of Palu, (5) there is no difference in performance of male and female official’s in The Inspectorate Office of Palu.